Studies of the mechanical and neutron shielding features of concrete by incorporation of green additive materials: Experimental and numerical study. (February 2022) - Hassanpour, Marzieh; Hassanpour, Mehdi; Rezaie, Mohammadreza; Salajegheh, Eysa; Iqbal Faruque, Mohammad Rashed; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: Concrete is one of the materials with a significant level of application in radiation shielding, especially in nuclear installations. However, the shielding features of concrete may vary depending on the composition of the concrete. In the present study, attempts have been made to assess the effects of the possible addition of two natural additives (hence 'green') - pistachios shell (PS) and date palm leaf (PL), in small dosages, as a partial replacement of conventional sand aggregates - on the neutron shielding properties of concrete mixes. Extensive numerical studies are made with Monte Carlo N-Particle code (MCNP-code) to investigate the influences of additives on neutron shielding performance of the candidate mixes for an assumed spherical geometry. Results are presented in terms of variation of the current transmission rate (CTR) and energy spectrum on assumed irradiation with a neutron beam. After initially comparing the NRS performance of the two materials under study, vis-à-vis four others - Cu, Li, Concrete, and Boron, the neutron shielding performance of concrete mixtures with increasing weight percentages of PS and PL incorporated in them have been assessed through the MCNP code. The results have indicated a general pattern for the neutron shielding with these mixtures, best performances achieved with a higher percentage of these green additives (10–15%). Mechanical strengths of the concrete samples with different weight percentages from 1% to 15% of PS and PL also have been experimentally investigated. The 7- and 28-days compressive strength optimized the concrete sample, however Cl with 1% of addition of PS- additive, has an acceptable, marginally lower compressive strength (6.33% and 6.87% at 7- and 28-days) as compared to the control concrete. Also, the density of the concrete was found to decrease with the increasing incorporation of PL and PS additives. Results thus have indicated that the incorporation of PS and PL additives in concrete can lead to quite enhanced shielding performance against the fast and thermal neutrons. As a result, the PL and PS additive materials may prove as a perfect replacement for expensive boron or enriched boron for neutron shielding application. Highlights: Mechanical and radiation shielding properties of concrete with two green additives are evaluated. Pistachios shell (PS) and date palm leaf (PL) are the two additive materials used herein. In numerical model, spherical geometry simulated by MCNPX as neutron shielding was studied. Results indicate that addition of PS and PL leads a better neutron shielding performance. Both PL and PS have a highest shielding percentage at spherical surfaces of radius >50 cm.